Can antioxidant responses be induced by habitat fragmentation process?. Issue 9 (7th July 2022) - Bani, Luciano; Orioli, Valerio; Giacchini, Roberto; Parenti, Paolo; Dondina, Olivia; Prokić, Marko; Faggio, Caterina; Campli, Giulia
Abstract : Animal populations are increasingly forced to live in small residual natural or semi‐natural areas due to habitat loss and fragmentation. Here, the viability of populations is often compromised by intrinsic threat factors typical of small and isolated populations, such as inbreeding depression, genetic drift and environmental and demographic stochasticity. Under these circumstances, organisms may have low fitness due to inadequate physiological responses needed to face environmental challenges. However, few studies have investigated the relationship between habitat fragmentation and stress defences. In this study, we aimed to test whether an increase in the level of individual inbreeding produced an increase in the antioxidant system response. To this purpose, we genotyped 151 individuals of fire salamander Salamandra salamandra (Amphibia: Urodela) within five sampling populations, located in forest landscapes with different degree of fragmentation in northern Italy. For 113 individuals we also measured the glutathione‐S‐transferase (GST) and catalase (CAT) enzyme activity. Results showed a significant increase in individual GST activity for increasing levels of inbreeding, whereas no relationship was found for CAT. We also measured acetylcholinesterase to test the possible confounding effects of pesticides that might have occurred in fragmented landscapes with forests interspersed with agricultural areas. However, no difference in this enzyme activity was found among sampling populations. We argue that high levels of GST activity may be symptomatic of oxidative stress derived from inbreeding. An increased frequency of homozygous deleterious alleles due to inbreeding may cause homeostatic alterations and trigger the expression of GST for protection against hydrogen peroxide reactive oxygen species. We suggest using GST as a biomarker for environmental stressors with great caution and not to underestimate that the sources of stress deriving from habitat fragmentation could lead to an unbalance in the oxidative status, possibly increasing population susceptibility to infectious diseases and, potentially, spillover events and zoonoses.